An Analysis of Grammatical Errors Made by the Teacher Professional Education Program (PPG) Students in Giving Explanation - Keke Rahmanela Fitri; Witri Oktavia (Journal of English Language Teaching, 2021)
This research was intended to analyze the most types of grammatical errors in giving explanation made by Teacher Professional Education Program Students (PPG). This research is descriptive research. It involved observing and describing the behaviour of a subject, also using the written data from teaching material of the students without influencing it in any way. The subjects of this research were 33 students from 1 class of Teacher Professional Education Program Students by using random sampling technique. The techniques of data collection were classroom observation-video recordings and written explanation from Teaching material of students. The findings of this research are the most type of grammatical errors in giving explanation made by Teacher Professional Education Program Students is omission, with 62 errors (47% of the total errors).